2019
DOI: 10.3390/ani9090698
|View full text |Cite
|
Sign up to set email alerts
|

Improvement of Oxidative Status, Milk and Cheese Production, and Food Sustainability Indexes by Addition of Durum Wheat Bran to Dairy Cows’ Diet

Abstract: Simple SummaryIn the near future, the expected increase in world population will enhance feed versus food competition between animals and humans to face the increasing demand by humans. For this reason, it is of paramount importance to feed ruminants with sources alternative to those representing themselves foods for humans. Durum wheat bran (DWB), similar to other by-products of the agri-food industry, can meet this need, its fiber content is high and represents also a remarkable source of phenolic acids, esp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 69 publications
1
26
0
Order By: Relevance
“…Indeed, several strategies, including the intake of polyphenol-rich plants or their extracts, have been proposed to modulate ruminant oxidative status. An improvement of OSI was also detected in dairy cows that, after 100 days of lactation, were supplemented with durum wheat bran, rich in phenolic acids [26]. For example, Yerba Mate supplementation, a plant with high polyphenol concentration, seems to improve the redox balance of early-lactation cows, as reflected by a reduction of OSI value [54].…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Indeed, several strategies, including the intake of polyphenol-rich plants or their extracts, have been proposed to modulate ruminant oxidative status. An improvement of OSI was also detected in dairy cows that, after 100 days of lactation, were supplemented with durum wheat bran, rich in phenolic acids [26]. For example, Yerba Mate supplementation, a plant with high polyphenol concentration, seems to improve the redox balance of early-lactation cows, as reflected by a reduction of OSI value [54].…”
Section: Discussionmentioning
confidence: 92%
“…Several studies reported that polyphenol dietary intake increases superoxide dismutase (SOD) in cows supplemented with grape skins [24] and in growing goats supplemented with juniper oil [25]. Moreover, the durum wheat bran, fed at 10% or 20% of the supplement, due to its content in phenolic acids, especially ferulic acid, improved the oxidative status and antioxidants capacity of dairy cows and, as a consequence, of their derived cheeses [26].…”
Section: Introductionmentioning
confidence: 99%
“…Extraction of phenolic acids from feeds samples (250 mg) was processed according to the procedure reported by Laddomada et al [25], which consisted of, in order, sample delipidation, alkaline hydrolysis, acidification and recovery in ethyl acetate; then, the extracts were dried under nitrogen flux, re-dissolved in 200 µL of 80:20 methanol/water, and analysed in an Agilent 1100 Series HPLC-DAD system (Agilent Technologies, Santa Clara, CA, USA). Separation and identification of peaks were performed as described by Bonanno et al [20].…”
Section: Methodsmentioning
confidence: 99%
“…While grain protein content, color and gluten strength are considered the most important features needed for use in pasta and bread production [14], DWB shows a high content of fiber and phenolic compounds, in particular ferulic acid with remarkable antioxidant properties [15,16,17,18,19]. The presence of polyphenols in the diet is undoubtedly advantageous to improving the oxidative state and hence the well-being of the animals [20,21]. In this regard, Wang et al [22] showed that a dietary supplementation of 80 mg/kg of ferulic acid was able to decrease the oxidative stress of lambs in cold environment and improve their growth performance.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, Bonanno et al [92] replaced cereal grains and legumes in the diet of dairy cows with durum wheat bran, at 6% and 13% of DMI. The by-product also affected heFCE and NFP, with the best results at the higher inclusion rate.…”
Section: Feed Conversion Efficiencymentioning
confidence: 99%